Highly Loaded Reactive Oxygen Species–Responsive Theranostic Lenvatinib‐Prodrug Nanoparticles Produced by Dispersion Polymerization - Sarah Spiewok; Felicitas Jansen; Jiaying Han; Markus Lamla; Max von Delius; Christian Trautwein; Laura De Laporte; Alexander J. C. Kuehne (Advanced NanoBiomed Research)
Nanoparticles represent a powerful class of materials for drug delivery, leveraging their small size for passive targeting through the enhanced permeability and retention effect in tumors. This universal approach in tumor targeting offers several advantages over free therapeutics, particularly when combined with imaging capabilities. While a plethora of nanoparticles exist for various imaging techniques, the number of nanoparticles with therapeutic functions is much smaller, due to the synthetic challenges present for incorporation and release of an active drug. Herein, a strategy to transform the tyrosine kinase inhibitor lenvatinib into a polymerizable prodrug monomer is presented, enabling its incorporation into biodegradable polyimidazole‐based particles. This drug monomer is then polymerized and thus incorporated into the nanoparticles via direct arylation in a dispersion polymerization approach. The polyimidazole backbone allows for high drug loads of up to 90 wt%. Additionally, the photoacoustic properties of the polyimidazole nanoparticles are preserved after drug incorporation. Moreover, the backbone remains degradable upon exposure to hydrogen peroxide, facilitating drug release. This approach enables packaging of a drug, for which no prodrug approaches exist and which is therefore challenging to incorporate into particles due to limited functional groups. The result is a new theranostic nanoagent.